2020
DOI: 10.1186/s12864-020-06793-7
|View full text |Cite
|
Sign up to set email alerts
|

Coding and long non-coding RNAs provide evidence of distinct transcriptional reprogramming for two ecotypes of the extremophile plant Eutrema salsugineum undergoing water deficit stress

Abstract: Background: The severity and frequency of drought has increased around the globe, creating challenges in ensuring food security for a growing world population. As a consequence, improving water use efficiency by crops has become an important objective for crop improvement. Some wild crop relatives have adapted to extreme osmotic stresses and can provide valuable insights into traits and genetic signatures that can guide efforts to improve crop tolerance to water deficits. Eutrema salsugineum, a close relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…These indicated that the identified genes could be the candidate genes for XZSN having higher drought resistance ability than LK3. In some plants, it was shown that the rapid and dramatic transcriptional reprogramming of the stress tolerance genotype contributes to higher stress resistance than the susceptible genotype ( Dossa et al., 2017 ; Simopoulos et al., 2020 ; Waititu et al., 2021 ; Yang et al., 2021 ). Interestingly, among these identified genes, over 90% of the genes were identified at drought treatment for 5 days, and over half of them in LK3 were not induced or inhibited at drought treatment for 5 days but were obviously upregulated or downregulated at drought treatment for 7 days ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…These indicated that the identified genes could be the candidate genes for XZSN having higher drought resistance ability than LK3. In some plants, it was shown that the rapid and dramatic transcriptional reprogramming of the stress tolerance genotype contributes to higher stress resistance than the susceptible genotype ( Dossa et al., 2017 ; Simopoulos et al., 2020 ; Waititu et al., 2021 ; Yang et al., 2021 ). Interestingly, among these identified genes, over 90% of the genes were identified at drought treatment for 5 days, and over half of them in LK3 were not induced or inhibited at drought treatment for 5 days but were obviously upregulated or downregulated at drought treatment for 7 days ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…A completely different approach could be to focus on pathways and genes that are unique to a multifactorial stress combination [31]. An additional strategy could be to identify and study plants that are subjected to extreme and multifactorial stress conditions in nature (e.g., desert plants, plants growing under harsh conditions in industrial waste sites, salt marshes, and/or next to hot springs, and/or some invasive species) [84][85][86], and…”
Section: How Can We Develop Plants With Enhanced Tolerance To Multifamentioning
confidence: 99%
“…Molecular phenotypes for transcriptional preadaptation associated with multiple abiotic stresses have been reported for S. parvula and E. salsugineum separately to highlight genes uniformly expressed before and after stress treatments compared to differential expression of orthologs in a stress sensitive sister species (Gong et al, 2005;Oh et al, 2014;Lee et al, 2016;Simopoulos et al, 2020;Wang et al, 2021;Pantha et al, 2021). Our work indicated that stressassociated functional gene clusters that exhibit transcriptional preadaptation in one extremophyte is in many instances contrasted by a dynamic induced response by the orthologs from the other extremophyte that ultimately match the expression level found in the preadapted species (e.g.…”
Section: Root Transcriptional Network Contain Multiple Divergent Points Between the Extremophytes With Convergent Outcomes For Stress-resmentioning
confidence: 99%